The influence of motivation, self-efficacy, and fear of failure on the career adaptability of vocational school students: Moderated by meaning in life - Chuang, Ya-Ting; Huang, Tzu-Huang; Lin, Shin-Yi; Chen, Bo-Ching (Frontiers in Psychology, 2022)
It is an important issue for vocational school students to have good adaptability for their future life. This study combines career construction theory and self-determination theory to construct a model to explore the relationship between the “motivation,” “self-efficacy,” “fear of failure,” “career adaptability,” and “meaning in life” of vocational school students. This study used a secondary data research method and retrieved a total of 2,377 data from vocational school students in Taiwan from the perspective of data exploration using PISA 2018 data, which was validated by the partial least squares structural equation model (PLS-SEM). The following results were obtained: 1) Vocational students were afraid that failure would have a negative impact on their career adaptability. 2) Motivation and Self-efficacy had a positive effect on career adaptability. 3) Motivation positively affected fear of failure. 4) Self-efficacy negatively affected fear of failure. 5) Meaning in life could positively moderate the effect of self-efficacy on fear of failure. 6) However, there was no statistical difference in the moderating effect of meaning in life on the relationship between motivation and fear of failure. First, fear of failure negatively affected career adaptability, while motivation and self-efficacy positively affected career adaptability; compared to the three effects, the negative effect of fear of failure may not be as great as expected. Second, motivation is like a double-edged sword as it improves adaptability, but it also comes with an increased fear of failure. On the contrary, self-efficacy can simultaneously improve the career adaptability of vocational students and reduce their fear of failure. Therefore, the development of self-efficacy should be given priority over motivation in the career adaptability enhancement strategy of vocational students. Finally, the meaning of life can positively moderate the negative influence of self-efficacy on the fear of failure. In other words, for vocational students with a low sense of self-efficacy, perhaps life education can be used instead as a strategy to reduce their fear of failure.